Composting evaluation of oil palm empty fruit bunches with palm oil effluent anaerobic sludge - Wan Razali, Wan Aizuddin (2014)
Oil palm empty fruit bunches (OPEFB) are one of the most abundant lignocellulosic biomass produced in palm oil industry throughout the year. With the increasing demand for palm oil worldwide, the amount of oil palm biomass available is expected to grow and composting is one of the best approaches to solve the abundance of this waste. Palm oil mill effluent (POME) is also produced in huge quantities because the ratio of water required to the oil palm fresh fruit bunches (OPFFB) processed is usually 1:1 ratio. Hence, this project was conducted to evaluate the pressed-shredded OPEFB and palm oil mill effluent (POME) anaerobic sludge composting treatment. The project was divided with three stages: 1) Composting process by windrow system at pilot scale; 2) Combinational in-vessel and windrow system at pilot scale; and 3) Composting of OPEFB with formulating palm oil mill effluent biochar solution (POMEBS) aerobic sludge using a lab scale in-vessel composter. All the composting process was completed within 40 days. The process performance was further evaluated by structure degradation analysis using scanning electron microscopy (SEM), Fourier transform infrared (FTIR), Thermogravimetric analysis (TGA) and X-ray diffraction (XRD). The windrow system managed to produce compost with final nutrient contents of N:P:K at 2.6:0.7:3.2 and the final C/N ratio was 14.62. Combinational in-vessel and windrow system produced compost with final N:P:K which stabilized at 2.8:0.4:2.8 and the final C/N ratio was 13.85. Composting OPEFB and POMEBS aerobic sludge managed to produce compost with higher N:P:K which stabilized at 3.7:0.8:6.2 and the final C/N ratio was 10.16. For windrow system, SEM pictures showed that silica bodies were completely removed at day 10 while for combinational in-vessel and windrow system SEM showed silica bodies only partially removed after 7 days after come out from the composter and completely removed after day 20. FTIR results illustrated the chemical reaction of the composting process for transforming OPEFB into mature compost. The results from FTIR were also correlated with XRD and TGA. TGA results showed that composting of OPEFB with POMEBS aerobic sludge have a higher weight reduction of organic matter compared to composting of OPEFB with POME anaerobic sludge which were 21% and 10% respectively. Microbial community analysis by Polymerase Chain Reaction-Denaturing Gel Gradient Electrophoresis (PCR-DGGE) indicated that bacillus subtilis strain TU2, bacillus Sp. MH-16, uncultured bacterium clone, uncultured firmicutes bacterium, bacillus Sp. Hs-v2, bacterium FA_149 and bacillus subtilis strainTBR2 were the predominant species at the optimum condition of the POMEBS aerobic sludge. In conclusion, composting OPEFB with POMEBS succeed in improving the degradation process and produced good quality compost.